Columbite-Tantalite Group Mineral U-Pb Geochronology of Chaqiabeishan Li-Rich Granitic Pegmatites in the Quanji Massif, NW China: Implications for the Genesis and Emplacement Ages of Pegmatites - Pan, Tong; Ding, Qing-Feng; Zhou, Xuan; Li, Shan-Ping; Han, Jie; Cheng, Long (Frontiers in Earth Science, 2021)
The Chaqiabeishan area is characterized by small Li-rich granitic pegmatites in the Quanji Massif, northwest China. In this study, the columbite-tantalite group minerals (CGMs) from a typical Li-rich pegmatite dike were analyzed for major element contents using EMPA (electron microprobe analyzer), for trace element contents using LA-ICP-MS (laser ablation-inductively coupled plasma mass spectrometry), and for ages using LA-ICP-MS U-Pb dating, respectively. The CGMs from the sample can be divided into two types, i.e., magmatic Type 1 and metasomatic Type 2. Although these two types of CGMs do not exhibit distinct major and trace element variations from core to rim within an individual grain, the Ta# values, Mn# values, and some trace element contents (such as Zr, Hf, W, Sr) of the Type 1 CGMs are distinct from those of the Type 2 CGMs. The overall compositional changes from the Type 1 CGMs to the Type 2 CGMs are consistent with the typical evolutionary trend described for many lithium-cesium-tantalum (LCT) pegmatites and the complex spodumene trend described by Černý et al. (1989). The Type 2 CGMs have formed later and must be a metasomatic product of the Type 1 CGMs. Eighteen Type 1 CGMs yielded a weighted mean 206Pb/238U age of 240.6±1.5 Ma. The slight oscillatory zoning and/or sector zoning suggest that the dated Type 1 columbites have a magmatic origin. Thus, the crystallization ages of the Type 1 columbites represent the emplacement ages of the Li-rich pegmatites. One of the Type 2 CGMs yielded a 206Pb/238U age of 211.0±4.7Ma, which is hardly interpreted to be an age representing the later hydrothermal metasomatism, because one data set has no apparent statistical significance. Therefore, our dating results can only indicate that the Li-rich pegmatite-forming melts were emplaced at approximately 240.6 Ma. Based on these results and previous studies of the 240–254 Ma granitoids in the QM, we conclude that the 240.6 Ma Li-rich granitic pegmatites, as well as 240–254 Ma granitoids in the QM, were both emplaced during the southward subduction of the Zongwulong Ocean Plate in the Late Permian to Middle Triassic.